T cell activation and function investigated using fully-defined 3D culture - Sica, Ilona (2024)
3D culture is gaining recognition as the advanced in vitro culture system to study cells. It bridges planar culture (2D culture) and in vivo studies, which could overcome oversimplified environment settings and genetic/physical differences to humans by animal models. For example, planar culture plates lack the architecture of tissues with extracellular matrix (ECM), whereas mouse tumours are poor representations of human ones. T cells are part of the immune system, and various studies have been conducted to understand their role in healthy or diseased tissues and the efficacy of therapies targeting these cells. To get more constructive in vitro results, by avoiding oversimplified culture (or in some cases animal models), 3D culture could be used by selecting appropriate biomaterial to study cells. Various biomaterials were tested for 3D T cell culture, enabling observation of cell-cell interaction, migration, effector function, and the effect of the microenvironment (i.e. oxygen gradient, stiffness) on cells. However, some of them have limitations such as modified environment (e.g. collagen hydrogel), tumour origins (e.g. Matrigel), poor stiffness level control or even immunogenic properties which could activate an unwanted immune response. In this case, self-assembling peptide gel offers solutions to those common biomaterial problems and makes it a great candidate for T cell 3D culture.